2024
DOI: 10.1519/jsc.0000000000003937
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Change of Direction Movement Demands in Professional Tennis Matchplay: An Analysis From the Australian Open Grand Slam

Abstract: Giles, B, Peeling, P, and Reid, M. Quantifying change of direction movement demands in professional tennis matchplay: An analysis from the Australian Open Grand Slam. J Strength Cond Res 37(7): 1419–1427, 2023—Change of direction (COD) contributes significantly to the movement repertoire of professional tennis players, yet the time-motion and degree demands of these changes are poorly understood. This study examines the velocity, acceleration, and angular displacement profiles of COD movements in modern profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Given that COD testing is often conducted to determine potential strengths and weaknesses that might benefit or harm an athlete's sport-specific performance, it is frequently recommended that the COD test of choice is relevant to the demands of the sport (50,103). Several studies have assessed the demands of tennis match play (1,(25)(26)(27)32,(35)(36)(37)(38)40,41,47,48,55,71,72,78,(89)(90)(91), concluding that the average point in tennis lasts between 3.8 and 12.1 seconds (41,55), during which tennis players cover 5.3-15.0 m (32,89). As for COD-specific demands, to the knowledge of the authors, only 2 studies have investigated the number of directional changes per point (25,41).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given that COD testing is often conducted to determine potential strengths and weaknesses that might benefit or harm an athlete's sport-specific performance, it is frequently recommended that the COD test of choice is relevant to the demands of the sport (50,103). Several studies have assessed the demands of tennis match play (1,(25)(26)(27)32,(35)(36)(37)(38)40,41,47,48,55,71,72,78,(89)(90)(91), concluding that the average point in tennis lasts between 3.8 and 12.1 seconds (41,55), during which tennis players cover 5.3-15.0 m (32,89). As for COD-specific demands, to the knowledge of the authors, only 2 studies have investigated the number of directional changes per point (25,41).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the demands of tennis match play (1,(25)(26)(27)32,(35)(36)(37)(38)40,41,47,48,55,71,72,78,(89)(90)(91), concluding that the average point in tennis lasts between 3.8 and 12.1 seconds (41,55), during which tennis players cover 5.3-15.0 m (32,89). As for COD-specific demands, to the knowledge of the authors, only 2 studies have investigated the number of directional changes per point (25,41). These studies observed that players perform an average of 1.5-2.5 directional changes per point (25,41).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations